Soil Microbial Distribution Depends on Different Types of Landscape Vegetation in Temperate Urban Forest Ecosystems - Fu, Qiang; Shao, Yizhen; Wang, Senlin; Liu, Fengqin; Tian, Guohang; Chen, Yun; Yuan, Zhiliang; Ye, Yongzhong (Frontiers in Ecology and Evolution, 2022)
Although soil microbes play an important role in the functioning of the forest ecosystem, our understanding of the spatial distribution characteristics of soil microbes among different vegetation types in urban forest ecosystems is poor. In this study, with the help of high-throughput sequencing, we examined the vegetation type preferences of soil microbes (fungi and bacteria) and then analyzed the microbe–environment (plant community, light availability, soil properties) relations in a temperate urban forest in China. Our results showed that the soil microbial (bacterial and fungal) richness of deciduous forest was higher than that of evergreen, deciduous, and mixed forests. The spatial distribution of fungi was more specialized than that of bacteria among different vegetation types. The driving forces of environmental factors on soil bacteria and fungi were different. Our findings suggest that different vegetation types favor the occurrence of different microbes, and the relationships between soil microbes and environmental factors depend on different vegetation types in this temperate urban forest. These findings shed new light on the biodiversity conservation of microbes in temperate urban forests and point to the potential importance of vegetation types for microbe formation.